Implementasi E-Modul Fisika Berbasis Kearifan Lokal Pembuatan Lapek Sarikayo terhadap Kemampuan Berpikir Kritis - Putri Mardiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to systematically examine the effectiveness of the implementation of Physics e-modules based on local wisdom on students’ critical thinking skills. The focus of The study is directed at the integration of local cultural values, especially through the context of making lapek sarikayo, as part of contextual and meaningful physics learning. The method used is Sstematic Literature Review (SLR), which is carried out through the Identification, selection, and analysis of 20 national scientific articles published in the last Five years. The analyzed articles were selected based on relevance to the topic of physics e-Modules, ethnoscience approaches or local wisdom, and measurement of critical thinking Skills. The results of the study show that e-modules that contain elements of local culture are able to increase student involvement,strengthen understanding of physics concepts, and significantly encourage critical thinking skills. A contextual approach through local culture is proven to provide a learning experience that is closer to the reality of learners. These findings have an important impact on the development of innovative teaching. Materials that are relevant to local cultural characteristics, as well as being a strategic reference in designing holistic and transformative 21st-century physics learning.